2017
DOI: 10.18844/gjs.v7i1.2363
|View full text |Cite
|
Sign up to set email alerts
|

IFRS integration into accounting curriculum: Undergraduate accounting students’ perceptions in Jakarta

Abstract: Abstract This study was to analyze the empirical evidence about the difference perceptions of IFRS into accounting curriculum integration between female students with male students, and students who are under or equal to 20 years with a student over the age of 20 years. Survey I conducted by distribution of a set questionnaires using purposive sampling method to accounting unfergraduate students of some university with A Accreditation Jakarta. Research Results state that there is a difference between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…They found that while IAS/IFRS courses are offered commonly in Turkey, only a few related courses are offered in the world. Ediraras et al (2017) analyzed the differences in perceptions of IFRS integration into accounting curriculum between female students with male students, and students who are under or equal to 20 years with a student over the age of 20 years in Indonesia. Their results stated that there was a difference between the perception of female students with male students about the integration of IFRS into accounting curricula, and there is no difference in perception between students aged below or equal to 20 years with a student over the age of 20 years.…”
Section: Status Of the Incorporation Of Ifrs Into Accounting Curriculamentioning
confidence: 99%
See 3 more Smart Citations
“…They found that while IAS/IFRS courses are offered commonly in Turkey, only a few related courses are offered in the world. Ediraras et al (2017) analyzed the differences in perceptions of IFRS integration into accounting curriculum between female students with male students, and students who are under or equal to 20 years with a student over the age of 20 years in Indonesia. Their results stated that there was a difference between the perception of female students with male students about the integration of IFRS into accounting curricula, and there is no difference in perception between students aged below or equal to 20 years with a student over the age of 20 years.…”
Section: Status Of the Incorporation Of Ifrs Into Accounting Curriculamentioning
confidence: 99%
“…He further found that departmental support, familiarity with IFRS, training and teaching experience in IFRS are positively associated with the time spent on teaching the IFRS. Ediraras et al (2017) showed that the problems that facing the incorporating of IFRS into accounting curricula in Indonesia were limited lecturing materials (textbooks) owned by educational institutions, lecturing time, and abilities / skills of lecturers. Aldredge (2018) investigated potential relationships among five independent variables (educator rank, institution size, IFRS familiarity, IFRS uncertainty, timing of U.S. IFRS adoption) and IFRS course coverage in the USA and found that only one factor, IFRS familiarity, was significantly related to IFRS course coverage.…”
Section: Factors Affecting Incorporating Ifrs Into Accounting Curriculamentioning
confidence: 99%
See 2 more Smart Citations